Electrosynthess and Characterization of Iron Oxide Nano-Composite Superparamagnetic Thin Films - Turcott, Shane R. (My University, 2004)
Using a newly developed method of co-electrodeposition, superparamagnetic films containing iron oxide nano-particles in a polymer matrix have been fabricationed. The method is based upon the electro synthesis of inorganic particles dispersed within a polymer matrix obtained by electrophoretic deposition. The results showed the prepared materials to exhibit superparmagnetic properties at room temperature. The influence of the deposition conditions and the electrolyte composition on the magnetic properties of the film have been studied. Adjusting the polymer content within the electrolyte has been shown to control the iron oxide to polymer composition ratio in the deposited film. This significantly affects the particle size, inter-particle distance and magnetic properties of the material. TGA analysis was used to determine the iron oxide to polymer composition ratio. The morphology of the films was studied by SEM and AFM techniques. Two theoretical approaches have been used to calculate the particle size in the developed films and the results are in good agreement with TEM observations. Saturation magnetization ranged up to 19.71 emu/g at room temperature in the films obtained. The blocking temperatures have been determined from the results of DC and AC measurements, the latter performed from 10 to 10,000 Hz. Blocking temperatures varied with film composition but remained below 111ºK. These results set the framework for discussion of the structure and magnetic properties of nano-materials synthesized using this fabrication method.
Keywords: Materials Science and Engineering; Materials Science and Engineering